The Apologizing Utterances of the Characters in “Failure to Launch” Movie - Padmasari, Arumtyas Puspitaning; Simanjuntak, Nensy Megawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
Communication is essential in expressing the desires of humans, as their lives are intertwined with it. Producing speech acts is what happens when we interact with others. This study employed a descriptive qualitative approach to analyze qualitative data. The movie